PENINGKATAN BUDAYA LITERASI PESERTA DIDIK MELALUI PROGRAM KERJA PENGADAAN TAMAN BACA DI SDN BANCONG KECAMATAN WONOASRI KABUPATEN MADIUN - Ima Kusumaningrum; Febiola Dwi Miranda; Aqwamith Thariq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low reading interest of students, especially at SDN Bancong. This low reading interest of students is caused by limited literacy support facilities and the lack of comfortable space for students to read. This research aims to improve students' reading literacy skills, to optimize the function of the reading garden as a center for school literacy activities, and to encourage students to use their free time productively. This research also aims to describe the implementation of the work program for the provision of a reading garden as an effort to improve the literacy culture of students at SDN Bancong. The method used in this research is descriptive qualitative with a participatory approach. Data were collected through direct observation, interviews with teachers and students, and documentation of activities. The program stages include observation, planning, coordination with the school, grouping books according to type, preparing tools and materials for the design of the reading garden, decorating the reading garden, inaugurating the reading garden, and activating the reading garden through routine literacy activities. The results of the study indicate that the provision of a Reading Garden at SDN Bancong has succeeded in increasing students' enthusiasm for reading, which can be seen from the increase in the frequency of student visits to the reading garden during break time. Furthermore, creating a comfortable and educational learning environment has been shown to transform students' perceptions of reading as a pleasurable activity. The conclusion of this study is that creatively managed Reading Gardens effectively stimulate the development of a culture of literacy from an early age in elementary schools.